Androgen‐repressed lncRNA LINC01126 drives castration‐resistant prostate cancer by regulating the switch between O‐GlcNAcylation and phosphorylation of androgen receptor - Yi Cai; Minfeng Chen; Yuchen Gong; Guyu Tang; Zhiwei Shu; Jiaxian Chen; Hengfeng Zhou; Yao He; Zhi Long; Yu Gan (Clinical and Translational Medicine, 2024)
Abstract Background Prostate cancer (PCa) initially shows satisfactory response to therapies targeting the androgen receptor (AR). However, progression to a castration‐resistant stage indicates poor prognosis in PCa patients. AR signalling still plays a central role in most castration‐resistant prostate cancers (CRPC). Therefore, unveiling the mechanisms of AR reactivation under androgen‐deprived conditions is imperative to discover novel therapeutic targets for CRPC. Methods Using an integrative analysis of the transcriptomics of three independent PCa cohorts and a published landscape of AR‐regulated long non‐coding RNA (lncRNA), lncRNA LINC01126 was selected as a candidate gene that could drive CRPC progression for further study. Quantitative reverse transcription polymerase chain reaction, in situ hybridisation (ISH) and fluorescent ISH were performed to detect LINC01126 in PCa tissues and cells. The functional role and mechanism of LINC01126 were further investigated using in vitro and in vivo gain and loss of function assays. Results LINC01126, identified as an AR‐repressed lncRNA, was significantly upregulated after AR‐targeted therapies. In addition, we found that LINC01126 was upregulated in CRPC and was associated with poor prognosis. We also proved that LINC01126 stabilised AR protein and enhanced AR nuclear translocation and transactivation by promoting the transition from O‐GlcNAcylation at threonine 80 to phosphorylation at serine 81 (S81) within the AR protein. Mechanism analysis revealed that LINC01126 facilitates the interaction of CDK9 with AR and impedes the binding of O‐linked N‐acetylglucosamine (O‐GlcNAc) transferase to AR. Consequently, LINC01126 expression was sufficient to activate AR signalling without androgen. LINC01126 overexpression increased, whereas LINC01126 knockdown decreased castration resistance traits in PCa cells in vitro and in vivo. Furthermore, our data showed that LINC01126‐targeting antisense oligonucleotides (ASO) substantially inhibited CRPC cells in vitro. Conclusions Our research expands the functions of AR‐regulated lncRNA in sustaining androgen‐independent AR activity and promoting CRPC progression and reveals that LINC01126 may be a new therapeutic target for PCa.